Tuning up FOIL for extracting information from the web. (6th January 2009) - Palacios, Pablo; Fernandez de Viana, Inaki
Most websites are designed to be easily understood by human users. This constitutes a problem when you want to access this information automatically. To resolve this problem, different algorithms have emerged to automatically generate and extract information. One of these algorithms is SRV; SRV uses a technique of supervised learning that is expensive in time. In this paper we present various optimisations to reduce this cost by up 40%.